Representasi Relasi Manusia dan Alam dalam Naskah Drama Di Bawah Bayang-Bayang Pohon Bakau Karya Wahyudin - Mandiri, Kanahaya Wisetyo Putri; Feliyanti, Rina; Rahayu, Artika Dita; Putri, Saski Ramdani Widia; Rizky, Auzia Fadhila; Anggraeni, Herba Anggun Wilma; Viraningsih, Amanda (GERAM (Gerakan Aktif Menulis), 2025)
This study examines the representation of the relationship between humans and nature in the drama script “Di Bawah Bayang-Bayang Pohon Bakau” by Wahyudin, utilizing ecocritical theory as an analytical lens and hermeneutics as an interpretative instrument. The focus of this study lies on three main dimensions: (1) human efforts in preserving nature, (2) human dependence on nature, and (3) the inner emotional bond between humans and nature. The results show that the main character's actions represent environmental conservation through the routine of planting mangroves to protect coastal areas from abrasion. Data findings reveal that human dependence on nature is fundamental, as demonstrated through character dialogues regarding the use of rainwater for household consumption and dry twigs as a source of livelihood. Furthermore, there is a deep emotional bond evidenced by the character's concern for marine degradation and the decision to remain in their homeland. Through the lens of eco-literacy, this script educates readers that the relationship between humans and the environment is not merely about a place to live, but an emotional attachment that determines sovereignty over water, food, and living space in the future.